DETERMINAN PENGARUH EKSPOR, IMPOR DAN PRODUK DOMESTIK BRUTO TERHADAP CADANGAN DEVISA INDONESIA - Dwi Puji Rahayu; firdayetti firdayetti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
This research is designed analyze the influence of export, import and Gross Domestic Product (GDP) factors on Indonesia's Foreign Exchange Reserves in 1990-2019. In this study we use 30 observations. The dependent variable in this study is Indonesia's foreign exchange reserves, while the independent variableare exports, imports and Gross Domestic Product (GDP). To see the effect of the independent variable on the dependent variable, we use multiple linear regression analysis. Based on the result of determination coefficient, we can conclude that simultaneously all of independent variables (exports, imports and GDP) jointly affect the combined variable (Indonesian foreign exchange reserves) in 1990-2019. The export variable has a positive effect on Indonesia's foreign exchange reserves. Important variables have a significant effect on Indonesia's foreign exchange reserves and the Gross Domestic Product (GDP) variable has a significant effect on Indonesia's foreign exchange reserves.